HBR Guide to Work-Life Balance - Harvard Business Review (Harvard Business Review Press, 2019)
Every day you juggle the many components that fill your life. Between work and family commitments, volunteer work, hobbies, and managing your physical and mental health, it's easy to feel overwhelmed and that you’re letting someone down or neglecting some aspect of your life. But you can find ways to honor all of your commitments without collapsing. The HBR Guide to Work-Life Balance will help you : Evaluate and adjust your priorities. Manage expectations. Set and spend your time budget. Make plans--and backup plans. Understand how to make trade-offs. Prioritize self-care. Discover what works for you